Local strain measurement in tensile test for an optimized characterization of packaging steel for finite element analysis - Knieps, Fabian; Köhl, Manuel; Merklein, Marion (Key Engineering Materials, 2021)
The continuous development of packaging steels for thickness reduction processes requires an advanced process design. This process is increasingly supported by finite element analysis to simplify tool construction and material selection purposes. Therefore, the fundamental basis is always the precise material characterization of packaging steel commonly based on tensile tests to determine flow curve and Lankford coefficients. However, due to strong temper rolling and the occurrence of slip bands, most packaging steels just show little elongation in tensile test. Therefore, a method of Paul et al. [1] to determine the flow curve with digital image correlation (DIC) methods in the necking zone was applied in this work to meet the requirements of packaging steel. For the use of anisotropic yield functions, it is necessary to determine Lankford coefficients. Thus, a new method is proposed to measure Lankford coefficients locally with a DIC system in tensile test, also in case that no homogenous forming condition is reached. With the presented approaches the packaging steel TH415 was characterized. In order to validate the developed methods, a demonstrator was simulated with anisotropic yield function Yld2000-2d [2]. The comparison between simulation and experiment showed clear improvements in simulation accuracy when using the newly presented methods for packaging steel.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Anisotropy; Finite element method; Packaging steel